PELAKSANAAN PELAYANAN KESEHATAN DALAM UPAYA PEMENUHAN HAK WARGA BINAAN DI LEMBAGA PEMASYARAKATAN - Puspitasari, Jenitha Leoni (Journal of Correctional Studies, 2024)
An inmate is someone who is serving a criminal term and has the right to receive health services in accordance with statutory regulations. This research can be used as evaluation material regarding how Correctional Institutions carry out their duties to fulfill the rights of inmates regarding health services, by considering many aspects of applicable law and to find out what rights to health services are for prisoners or inmates. This research uses a normative legal method with secondary data sources in the form of the Law concerning Requirements and Procedures for Implementing the Rights of Correctional Inmates collected by means of literature study. The results of the research show that there are still obstacles in fulfilling the right to health services for inmates, so improvements still need to be made to comply with statutory regulations in correctional institutions.